Maize silk-based biostimulant seed priming enhances salt resilience and productivity in Zea mays by upregulating antioxidant defenses and targeted ion-transport genes - Amany H.A. Abeed; Hesham Alharby; Eman E.E. Belal; Ibrahim A.A. Mohamed; Shaymaa A.A. Badr; Mohamed A.M. Eid; Ali A.S. Sayed; Mostafa M. Rady; Ahmed Shaaban (Plant Science, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Preparation and evaluation of a monovalent Foot and Mouth Disease vaccine as a rapid response to the emerging serotype SAT1 in Egypt - Sonia A. Rizk; Hany I. Abu-Elnaga; Hend M. Daoud; Wael Mossad; Ehab El-Sayed Ibrahim; Mohamed A. Gamil; Nermeen G. Shafik; Mohamed S. Abousenna; Samir A. Nassif; Mohamed A. Saad (Veterinary Immunology and Immunopathology, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Therapeutic and research frontiers in fibromyalgia: integrating pathophysiology with innovative drug repurposing - Sheer A. Joodi; Dalia A. Nawwar; Nora O. Abdel Rasheed; Weam W. Ibrahim; Helmy M. Sayed (Inflammopharmacology, 2026)

Development of dry and oil-based formulations of Metarhizium anisopliae using carrier materials for effective control of red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nahdia Perveen; Abu Bakar Muhammad Raza; Muhammad Arshad; Panagiotis Eliopoulos; Samah F. Ibrahim; Mustafa Shukry; Samy Sayed; Hanan M. A. Hamada (BioControl, 2026)

Correction to: Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El‑Hanafy; Eman Hamza; Eslam Habba; Doaa A. El‑Hanafy; Nashwa Eltantawy; Reham A. Al‑Dhelaan; Kholoud H. Radwan; Abeer A. El‑Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Exploring the therapeutic potential of Lupeol isolated from Ochrosia elliptica Labill. leaves in polycystic ovarian syndrome - Essam Abdel-Sattar; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Shimaa R. Emam; Heba Hozyen; Marwa Zakaria; Samar M. Mouneir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El-Hanafy; Eman Hamza; Eslam Habba; Doaa A. El-Hanafy; Nashwa Eltantawy; Reham A. Al-Dhelaan; Kholoud H. Radwan; Abeer A. El-Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Macromodeling and experimental investigation of RC frames infilled with clay bricks and autoclaved aerated concrete blocks under cyclic loading - Ahmed M. El-Kholy; Huda Sayed; Ibrahim M. Metwally; Ayman A. Shaheen (Bulletin of Earthquake Engineering, 2026)
This study investigates the cyclic behavior of reinforced concrete (RC) frames infilled with autoclaved aerated concrete (AAC) blocks—a novel and environmentally friendly material—compared to traditional clay masonry infill commonly used in Egypt. In addition, the RC frames were reinforced with an advanced type of reinforcing steel designed to enhance seismic resistance. Three 2/3-scale RC frames were experimentally tested under cyclic lateral loading. Both infill types contributed approximately equally to increasing the lateral strength of the RC frame (around 60% improvement); however, the AAC infill significantly outperformed the brittle clay infill in terms of ductility enhancement. To characterize the response, trilinear and quadlinear backbone curves were developed for the clay and AAC infills, respectively. Alongside the experimental work, numerical macromodeling of the infill panel as multi-strut and single-strut macromodels using SeismoStruct and SAP2000, respectively, was conducted. Additionally, both concentrated and distributed plasticity approaches were employed to model the nonlinear behavior of the RC elements. A suitable constitutive steel model was used to numerically track the experimental hysteresis response of the steel reinforcement. The multi-strut macromodel demonstrated superior accuracy in capturing the hysteresis behavior of the infilled RC frames compared to the single-strut model. The strut width and its post-cracking degradation rate, the shear-to-axial stiffness ratio, and the strain in the infill at peak stress were key parameters influencing the accuracy of the complex multi-strut macromodel in distinguishing between the brittle behavior of clay infill and the ductile response of AAC infill.

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

Ursolic acid, a pentacyclic triterpene from Ochrosia elliptica Labill leaves and its role in the management of polycystic ovary syndrome (PCOS) - Shimaa R. Emam; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Heba F. Hozyen; Marwa Zakaria; Essam A. Abdel-Sattar; Samar M. Mouneir (Inflammopharmacology, 2026)
Ursolic Acid (UA), a naturally occurring pentacyclic triterpene, was isolated from Ochrosia elliptica . Polycystic Ovary Syndrome (PCOS) a prevalent endocrine disorder characterized by hyperandrogenism, insulin resistance, and chronic inflammation. In this study, we investigate the role of UA in alleviating the symptoms of PCOS, focusing on its biochemical, hormonal, and histopathological effects in a rat model. Using adult female Wistar Albino rats, PCOS was induced through letrozole administration. The rats were then treated with UA at two different doses (25 and 50 mg/kg), alongside a control group and a standard ovulation-inducing medication, clomiphene citrate (1 mg/kg). Biochemical analyses showed that PCOS induction significantly increased serum malondialdehyde (MDA) levels by approximately 1.21-fold, while markedly reducing superoxide dismutase (SOD) and catalase (CAT) activities ( p ≤ 0.05) by approximately 0.48-fold, relative to negative control. Treatment with UA (50 mg/kg) dose-dependently restored oxidative balance, reducing MDA (~ 0.82-fold) and elevating SOD (~ 2.39-fold) and CAT (~ 2.11-fold) activities toward PCOS values ( p ≤ 0.05). Hormonally, PCOS rats exhibited elevated luteinizing hormone (LH) and testosterone levels by approximately 1.70-fold, compared to the negative control ( p ≤ 0.05). Both doses of UA significantly lowered LH and testosterone, with the 50 mg/kg dose achieving reductions comparable to clomiphene citrate ( p ≤ 0.05). Histopathological examination showed improved ovarian morphology with reduced cystic follicles and increased corpus lutea in UA-treated groups. Furthermore, UA downregulated key genes involved in steroidogenesis and oxidative stress response, suggesting a multifaceted mechanism of action. The findings highlight UA’s potential as a novel therapeutic option for managing PCOS symptoms, emphasizing the need for further research into its efficacy and safety in clinical applications.

Failure Mechanisms of Helical Piles and Evaluation of Capacity Prediction Models - Nader Ibrahim; Sayed M. Ahmed; Mahmoud S. Hammad (Geotechnical and Geological Engineering, 2026)

Ultrasonic irradiation for ZnO NPs Synthesis and their hepatoprotective effect against acetaminophen induced hepatic toxicity in albino rats: Biochemical, physiological, and histopathological assessments - Yasmine A. Mansour; Fady Sayed Youssef; Shaymaa Hussein; Hanan F. AbdEl_Halim; Sameh H. Ismail; Gehad G. Mohamed; Abdelfattah M. Abdelfattah; Rasha M.M. Ezz-Eldin; Heba H. Mahboub; Sherin Ibrahim (Tissue and Cell, 2026)

Thiamine-functionalized magnetic coffee-derived carbon for efficient methylene blue removal: Synthesis, mechanism, and performance evaluation - Abdullah M. Aldawsari; Hassan M.A. Hassan; Mosaed S. Alhumaimess; Ibrahim Hotan Alsohaimi; Ayoub Abdullah Alqadami; Mohammad S. Algamdi; Mohamed Y. El-Sayed (Journal of Environmental Chemical Engineering, 2026)

Cerium oxide nanoparticles attenuate hepatic failure via blocking TGF-β/Smads and upregulating Nrf2/HO-1 signaling pathways in liver fibrosis rat model - Noha A. Mowaad; Sara M. Baraka; Saber Ibrahim; Doaa A. Mansour; Reda M. S. Korany; Ahmed F. El-Sayed; Arwa A. Hassan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
T his article is aimed at assessing the anti-fibrotic action of plant-based fabricated cerium oxide nanoparticles (CeO 2 NPs). The Carissa carandas aerial parts methanolic extract was utilized to prepare CeO 2 NPs, where the dispersal of particle size distribution and zeta potential value was 61.9 nm and − 18.94 mV, respectively, verifying the successful synthesis of CeO 2 NPs. In rats, CeO 2 NPs were intravenously injected at doses of 0.1 and 0.5 mg/kg twice a week for a month, in parallel with thioacetamide (TAA, 200 mg/kg, i.p). Our findings revealed that CeO 2 NPs alleviated the alteration in serum GPT, GOT, ALP, total bilirubin, albumin, and total protein levels induced by TAA. Additionally, the hepatic oxidative insult due to TAA was inferred by elevation in malondialdehyde and reduction of glutathione content, which in combination with downregulation of SIRT1, Nrf2, and HO-1 in hepatic tissues was improved by CeO 2 NPs. A clear repression in hepatic fibrosis was observed in CeO 2 NP-treated groups as demonstrated by significant downregulation in TGF-β1 and p-Smad 2 and 3 proteins and COL1A1, MMP-2, and α-SMA expressions in hepatic tissues. The histopathological outcomes exhibited a considerable accumulation of collagen fibers in hepatocytes in TAA-challenged rats, which was ameliorated by CeO 2 NPs. Also, CeO 2 NPs dampened the death of hepatic cells via blocking caspase 3 activation as indicated by the immunohistochemical results. The in silico investigations documented the powerful binding affinities of TGF-β1, COL1A1, MMP-2, p-Smad2, p-Smad3, SIRT1, Nrf2, and HO-1 proteins with CeO 2 NPs. In conclusion, this study emphasized the efficacy of CeO 2 NPs as a potent anti-fibrotic agent through upregulating SIRT1/Nrf2/HO-1 and downregulating TGF-β1/Smads pathways.

Development and characterization of BSA-pullulan gel matrices incorporating orange peel flavonoids: Structural interactions and antimicrobial and antioxidant functionalities - Mahmoud Salah; Mabrouk Sobhy; Yajing Fang; Salwa M. El-Sayed; Ibrahim Khalifa; Ali Korin; Mohammed Mansour; Syed Asim shah Bacha; Sajid Maqsood; Yun Wang (Food Chemistry, 2025)

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

MALAT1 SNP (rs619586) shows a protective effect against type 1 diabetes mellitus, while the miR-146a SNP (rs57095329) is linked to an increased risk of developing the disease - Soha M. Hamdy; Heba A. Ibrahim; Omayma O. Abdelaleem; Olfat G. Shaker; Sherin K. Hussein; Sara M. A. K. Massoud; Ola N. Sayed (Molecular Biology Reports, 2025)

Paleoenvironmental setting and facies analysis of the Middle Miocene carbonate platform in north Western Desert, Egypt - Ibrahim M. Ied; Sherif Farouk; Sayed Abd El-Azeam; Mohammad Abd-Elazez; Ibtsam A. Abd EL-Rauf (Carbonates and Evaporites, 2025)
The Marmarica Formation in the north Western Desert (NWD) of Egypt is predominantly composed of Middle Miocene carbonate rocks. A detailed microfacies and paleoenvironmental analysis was conducted on six representative surface sections extending from the Siwa to Matruh areas: Dakrur, North Siwa (NS), Siwa-Matruh 1 (SM1), Siwa-Matruh 2 (SM2), Abu Khrait, and Agiba. Field observations and lithological data indicate that the Marmarica Formation can be subdivided into three informal members: lower, middle, and upper. A distinct facies shift is observed from interbedded shale and carbonate in the Siwa area to predominantly carbonate facies towards the north in the Siwa-Matruh and Matruh areas. Microfacies analysis of the studied sections identified twelve distinct microfacies types, which are grouped into three main facies associations, corresponding to three paleoenvironmental settings: restricted lagoonal platform interior, open marine shelf (platform top), and high-energy platform shoal. Based on the vertical and lateral distribution of these facies, a homoclinal ramp depositional model is proposed, revealing a clear deepening trend from south to north. In the southern Siwa area, the depositional system evolves vertically from a protected, restricted lagoon to open shelf and shoal settings. Towards the north, the environment becomes progressively deeper, dominated by fluctuations between open marine shelf and high-energy shoal environments. Sequence stratigraphic analysis identified three third-order transgressive-regressive (T-R) depositional sequences (SQ1, SQ2, SQ3), each comprising transgressive system tracts (TST) and highstand system tracts (HST) and are separated by two sequence boundaries (SB1 and SB2). These sequences correspond to global eustatic cycles—such as Haq et al. 1987 and Hardenbol et al. 1998- and correlate with equivalent Miocene carbonate systems in the Tethyan realm highlighting the interplay of eustatic sea-level changes and regional tectonics on carbonate platform evolution during the Langhian–Serravallian stages.

Corrigendum to “Rational design of chitosan/guar gum/zinc oxide bionanocomposites based on Roselle calyx extract for Ras cheese coating” [Carbohydr. Polym., Volume 239, 1 July 2020, 116,234] - Samah M. El-Sayed; Hoda S. El-Sayed; Osama A. Ibrahim; Ahmed M. Youssef (Carbohydrate Polymers, 2025)

Poly(styrene-alt-chitosan malonate)/poly(ether sulfone) blend membranes for ultrafiltration with enhanced antifouling performance - Mosaed S. Alhumaimess; Ibrahim Hotan Alsohaimi; Raghad Ayed Alenazi; Mohamed Y. El-Sayed; Abdullah M. Aldawsari; M.R. El-Aassar; Ahmed A. Alshahrani; Hassan M.A. Hassan (Journal of Water Process Engineering, 2025)

Development of novel ferrocene-functionalized NH2-MIL-125 MOF for efficient photocatalytic degradation of indigoid dyes under visible light - Mostafa A. Sayed; Osama A.S. Rafea; Ali M. Abdel-Aziz; Reda M. Abdelhameed; Ibrahim H.A. Badr (Journal of Environmental Chemical Engineering, 2025)

Phage therapy and its role in cancer treatment and control - Heba Ibrahim Abd El-Moaty; Ahmed S. Doghish; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Mahmoud A. Elrebehy; Kareem AlFarsi; Amr M. Abdelfatah; Aly M. Waseem; et al. (Folia Microbiologica, 2025)

Biological, biochemical, hormonal effect, and histological perturbations of Procambarus clarkii (Crustacea: Cambaridae) hemolymph on Biomphalaria alexandrina snails - Salwa A. H. Hamdi; Sayed Abd El-Monem; Amina M. Ibrahim; Mona F. Fol; Nesma A. Mostafa (Aquaculture International, 2025)
Schistosomiasis is a severe illness carried by snails of the genus Biomphalaria , which have a large distribution in Egypt. Control of the intermediate host snail is critical in limiting schistosomiasis spread. On the topic of snails’ management, bioactive products extracted from aquatic invertebrates have gained more interest. Here, for the first time, the current research intended to identify the bioactive compounds present in hemolymph collected from the freshwater crayfish Procambarus clarkii and to assess its molluscidal activity against Biomphalaria alexandrina snails. Results showed that following exposure to the sub-lethal concentrations (LC 10 34.9 and LC 25 42.8 mg/l) of hemolymph, a reduction in survival and reproductive rates of B. alexandrina was detected, as well as a substantial increase in transaminases (AST and ALT) activities, while a reduction in total protein and albumin levels. Also, levels of testosterone and 17β-estradiol hormones decreased compared to the control group. Histopathological examination of the digestive gland of treated B. alexandrina displayed a shrinkage of the tubules and an increase in the inter-tubular spaces, and also, degeneration in the oocytes and spermatocytes of the hermaphrodite glands with a loss of connective tissues between the acini was observed. Thus, based on these results, a new strategy should be developed for a better use of these agents in schistosomiasis control.

Stage-wise monitoring of microplastics (MPs) in wastewater treatment plants (WWTPs): Abundances, characteristics, polymer types, and removal - Wenbo Kong; Mabkhoot Alsaiari; Mohammed Jalalah; Farid A. Harraz; Ibrahim M. Hegab; Maha Awjan Alreshidi; El-Sayed Salama (Process Safety and Environmental Protection, 2025)

Relationship Between Grain Yield Response Index and Wheat Genotypes Adapted to Nitrogen–Deficient Environments - Yassmin T. M. Emam; Afafa M. Tolba; Yasser A. El-Gabry; Ibrahim M. El– Metwally; Hani Saber Saudy; Amany N. Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Plant breeders of self-pollinated crops such as wheat often obtain huge number germplasms via hybridization programs. However, screening these germplasms to select the best ones, especially in terms of nitrogen (N) use efficiency, is not an easy task. Thus, the current study was designed to determine the significance of grain yield response index (GYRI) as a promising parameter versus the traditional agronomic traits to characterize the most efficient and responsive wheat genotypes to applied N. The study involved twenty bread wheat genotypes (six commercial varieties namely Sakha 94, Sakha 95, Giza 171, Gemmiza 12, Masr 1, Masr 2 and 14 new lines, numbered from 1 to 14). Over two seasons, the performances of these genotypes were monitored under three N levels: optimum N (192 kg N ha –1 , farmer practice), moderate deficit N (144 kg N ha –1 +biofertilizer) and high deficit N (96 kg N ha –1 +biofertilizer). The experiment was designed in split-plot and replicated thrice. Line 11 under optimum N or high deficit N and Line 4 under moderate deficit N in the first season as well as Line 14 under high deficit N in the second season had the earliest heading time. Under normal N application (192 kg N ha –1 ), Masr 1 in the first season and Gemmiza 12 in the second season had the widest flag leaf. Under moderate deficit N, Line 6 in the first season and Line 14 in the second one surpassed all other genotypes. Application of 144 kg N ha –1 +biofertilizer×Line 3 in the second season outperformed all other genotypes grown under the other N treatments. Line 9, Line 10, Line 13, Sakha 95 and Gemmiza 12 (under moderate deficit N) as well as Line 7, Line 8, Line 9, Line 13, Line 14, Gemmiza 12 and Masr 1 (under high deficit N) recorded the greatest values of grain yield in the first season. While, Sakha 95 and Line 9 were the marked genotypes for producing the maximum grain yield under moderate deficit N and high deficit N, respectively, in the second season. GYRI estimation exhibited that Line 11 and Sakha 95 in the first season and Sakha 95 and Masr 2 in the second one were the efficient and responsive genotypes for N applications. Obviously, GYRI as a breeding parameter can contribute greatly to resolving the conflict between crop traits in terms of distinguishing N-deficiency tolerant varieties. Herein, GYRI detected that Line 11, Sakha 95 and Masr 2 are considered promising germplasms to develop and improve wheat to tolerate low N supply. Further, the increased grain yield of some tested genotypes (i.e. Line 5, Line 6, Line 8, Line 9, Line 13, Line 14, Giza 171, Masr 1, Gemmiza 12) under deficit N than optimal N is an observation worthy of in-depth future investigation.

Impacts of PVC microplastic ingestion on Biomphalaria alexandrina: behavioral, physiological, and histological responses - Amina M. Ibrahim; Ahmed A. A. Hussein; Menna H. E. Morsy; El-Sayed Baz (Hydrobiologia, 2025)
Microplastic pollution has emerged to be a crucial environmental concern. Despite the growing body of research on microplastic ingestion in oceans and marine organisms, there is a knowledge gap concerning the effects of microplastic exposure on freshwater ecosystems, which support diverse communities of plants, animals, and microorganisms. The freshwater snail Biomphalaria alexandrina is a valuable model for dissecting the ecological impact of many pollutants in aquatic environments. This study aimed to investigate the impacts of ingesting microplastic particles on B. alexandrina , particularly focusing on polyvinyl chloride (PVC), widely used in plastic applications, piping, electrical, and vehicle equipment, which results in their frequent presence in ecosystems. A combination of behavioral, physiological, biochemical, and histological assessments revealed profound effects of microplastic ingestion by these mollusks. These effects include the accumulation of PVC particles in their intestines, a reduction in feeding behavior, decreases in survival and growth rates, disruptions in biochemical parameters, induction of oxidative stress, and histological damage to their digestive glands. Additionally, our data suggest that the adverse impacts are concentration-dependent, with higher PVC concentrations causing more severe harm. Our findings advance our understanding of the potential consequences of microplastic pollution in freshwater habitats and inform targeted mitigation strategies.

Synthesis and antimicrobial evaluation of a new hybrid bis-cyanoacrylamide-based-piperazine containing sulphamethoxazole moiety against rheumatoid arthritis-associated pathogens - Mona M. Soliman; Ahmed H. M. Elwahy; Ahmed M. Sayed; Mahmoud Ibrahim; Mohamed A. Dawoud; Shahd Hisham Mohamed Ali; Menna Tallah S. Nady; Nada A. Hassan; Wessam Saad; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Piperazine-based compounds have garnered significant attention due to their notable biological and pharmacological activities, making them essential in fine chemical and pharmaceutical applications. In this study, we managed to synthesize a novel hybrid bis-cyanoacrylamide bearing the piperazine core via phenoxymethyl linker and incorporating sulphamethoxazole moiety. The novel compound was fully characterized using different spectral data including 1H-NMR, 13 C-NMR, and FTIR spectroscopy. Piperazine-based compounds were screened for in silico studies to understand the antimicrobial activity against infections that may contribute to rheumatoid arthritis symptoms. The tested piperazine compound was also evaluated for its antimicrobial activity against Aspergillus niger , Candida albicans , Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 29213, Pseudomonas aeuroginosa ATCC 27853, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603. S. aureus showed the highest inhibition, with a zone diameter of 16.0 ± 1.0 mm at a concentration of 0.8 mg/ml. The minimal inhibitory concentration (MIC) for all bacterial species ranged from 5 to 40 mg/ml. In contrast, fungal species were the most resistant to the tested compound. Molecular docking studies were conducted to elucidate the interaction mechanisms, binding energies, and hydrogen bonding interactions within protein–ligand complexes. Molecular docking studies were performed against five bacterial proteins and two fungal proteins, including DNA gyrase subunit B (UniProt ID: Q839Z1), protein RecA of (UniProt ID: P0A7G6), cyclic AMP-AMP-AMP synthase (UniProt ID: P0DTF7), UDP-N-acetylglucosamine 1-carboxyvinyl transferase (UniProt ID: A0A1S5RKE3), and clumping factor A (UniProt ID: Q53653). The tested compound achieved the highest binding score of ∆G = − 10.9 kcal/mol at the cyclic AMP synthase active site (UniProt ID: P0DTF7), forming 26 interactions. The results demonstrated that the synthesized piperazine compound exhibits promising antibacterial and antifungal activities, highlighting its potential as a candidate for antimicrobial development.

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Potato Leaf Disease Classification Using Optimized Machine Learning Models and Feature Selection Techniques - Marwa Radwan; Amel Ali Alhussan; Abdelhameed Ibrahim; Sayed M. Tawfeek (Potato Research, 2025)
The diseases that particularly affect potato leaves are early blight and the late blight, and they are dangerous as they reduce yield and quality of the potatoes. In this paper, different machine learning (ML) models for predicting these diseases are analysed based on a detailed database of more than 4000 records of weather conditions. Some of the critical factors that have been investigated to determine correlations with disease prevalence include temperature, humidity, wind speed, and atmospheric pressure. These types of data relationships were comprehensively identified through sophisticated means of analysis such as K -means clustering, PCA, and copula analysis. To achieve this, several machine learning models were used in the study: logistic regression, gradient boosting, multilayer perceptron (MLP), and support vector machine (SVM), as well as K -nearest neighbor (KNN) models both with and without feature selection. Feature selection methods such as the binary Greylag Goose Optimization (bGGO) were applied to improve the predictive performance of the models by identifying feature sets pertinent to the models. Results demonstrated that the MLP model, with feature selection, achieved an accuracy of 98.3%, underscoring the critical role of feature selection in improving model performance. These findings highlight the importance of optimized ML models in proactive agricultural disease management, aiming to minimize crop loss and promote sustainable farming practices.

Assessing seawater intrusion impact on groundwater quality in El-Omayed aquifers, Mediterranean coast, Egypt using hydrogeochemical and chemometric analyses - Mohammed I.A. Ibrahim; Mohamed A. El-Sawy; Ahmed R. Elgendy; Hossam M. El-Sayed; Laila A. Mohamed; Mohamed A. Aly-Eldeen (Groundwater for Sustainable Development, 2025)

Structural and Energetic Insights into the Binding of L- and D-Arginine Analogs with Neuropilin-1 (NRP1): Molecular Docking, Molecular Dynamics and DFT Calculations - Mahmoud A. A. Ibrahim; Dina E. M. Mohamed; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Shaban R. M. Sayed; Mohamed A. El-Tayeb; Peter A. Sidhom; Paul W. Paré (Cell Biochemistry and Biophysics, 2025)

Paleobiodiversity, Paleobiogeography, and Paleoenvironments of the Middle–Upper Eocene Benthic Foraminifera in the Fayum Area, Western Desert, Egypt - Mostafa M. Sayed; Petra Heinz; Ibrahim M. Abd El-Gaied; Ramadan M. El-Kahawy; Dina M. Sayed; Yasser F. Salama; Mansour H. Al-Hashim; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
The middle–upper Eocene successions of northwest Fayum, Egypt, provide a crucial archive for reconstructing paleoenvironmental conditions and paleobiogeographical patterns of the southern Tethys realm. Stratigraphically, the investigated section is subdivided into three rock units: the Gehannam Formation (Bartonian-Priabonian), the Birket Qarun Formation, and the Qasr El Sagha Formation (Priabonian). A total of 101 benthic foraminiferal taxa, representing 31 genera, 23 families, 13 superfamilies, and four suborders, were identified. The middle–late Eocene age is primarily determined by the co-occurrence of index spinose planktonic foraminifera (Acarinina spp., Morozovelloides spp., and Globigerinatheka semiinvoluta) and benthic foraminiferal assemblages, further supported by the presence of the nannofossil marker Chiasmolithus oamaruensis. Four local benthic biozones are identified and correlated with coeval zones in nearby areas. Quantitative analyses of benthic foraminiferal individuals, diversity indices, ecological parameters, and the benthic foraminiferal oxygen index (BFOI) reveal distinct environmental shifts. The rock unit occupied by the late middle Eocene assemblages is diversified and dominated by calcareous infaunal taxa (e.g., Bolivina spp., Fursenkoina spp., and Nonionella spp.), indicative of low-oxygen outer neritic conditions associated with elevated organic influx. In contrast, the late Eocene Birket Qarun and Qasr El Sagha showed an increase in epifaunal forms and reduced diversity, suggesting a transition to dysoxic-oxic conditions. Paleobiogeographical analysis indicates a strong affinity with the Tethyan realm, with potential faunal exchange through the Trans-Saharan Seaway. These findings enhance our understanding of Paleogene marine connections between the Tethyan and Indo-Pacific realms, contributing to broader discussions on Eocene paleobiogeography and depositional dynamics in North Africa.

Comparative Neuroprotective Potential of Nanoformulated and Free Resveratrol Against Cuprizone-Induced Demyelination in Rats - Sara A. M. El-Sayed; Ghadha Ibrahim Fouad; Maha Z. Rizk; Hanan H. Beherei; Mostafa Mabrouk (Molecular Neurobiology, 2025)
Demyelination is a frequent yet crippling neurological disease associated with multiple sclerosis (MS). The cuprizone (CZ) model, which causes demyelination through oxidative stress and neuroinflammation, is a popular tool used by researchers to examine this process. The polyphenol resveratrol (RESV) has become a promising neuroprotective agent in seeking for efficient therapies. In a rat model given CZ, we created and examined iron oxide nanoparticles (IONPs) loaded with RESV (IONP-RESV) to see how effective they were as a therapeutic agent against free RESV. According to molecular mechanisms, exposure to CZ resulted in a marked downregulation of myelin proteolipid protein (PLP) expression and an overexpression of the inflammatory markers tumor necrosis factor-α (TNF-α) and S100β, which are indicators of demyelination and neuroinflammation. It is remarkable that these CZ-induced alterations could be reversed by therapy with either RESV or IONP-RESV. Interestingly, IONP-RESV showed even stronger anti-inflammatory activity, as shown by a more noticeable downregulation of TNF-α and S100β expression. These results were confirmed by histopathological examination of the cerebral cortices. Our findings support the better neuroprotective benefits of RESV-loaded IONPs over free RESV in reducing demyelination and neuroinflammation brought on by CZ. Owing to their pro-remyelinating, anti-inflammatory, and antioxidant properties, RESV-loaded IONPs show promise as a neurotherapeutic intervention in the future for neurological diseases such as multiple sclerosis. Graphical Abstract

Physiological and Molecular Responses of Red Amaranth (Amaranthus cruentus L.) and Green Amaranth (Amaranthus hypochondriacus L.) to Salt Stress - Tartil M. Emam; Abd Elaziz M. Hosni; Ahmed Ismail; Ramy G. El-Kinany; Mohammed Hewidy; Hani Saber Saudy; Mohamed M. A. Omar; Mariam T. S. Ibrahim; Shunzhao Sui; Salwa M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Salinization, as a serious climate change phenomenon, continues to cause critical issues for soils and crops. Abundance of genetic diversity of plants could contribute in solving the impacts of salinity. However, the relations between physiological and molecular traits of plant species need deep investigation and interpretation. Pot experiments were conducted in the greenhouse to investigate the difference in behavior between two amaranth species when they were beforehand subjected to salinity-stress conditions, specifically on some specific physiological and molecular characteristics. After 45 days from transplanting, salt stress was induced using a 150 mM sodium chloride solution. Treatments were arranged in randomized complete block design using three replications. After 0, 2, 6, 10, and 24 h, samples were collected to evaluate physiological data as well as diversity of gene expression. The samples were immediately frozen in liquid nitrogen and stored in -80⁰ C ultralow temperature refrigerators. Findings revealed that the red amaranth species ( Amaranthus cruentus ) was more tolerant to saline stress than the green amaranth species ( Amaranthus hypochondriacus ). Result data revealed that malondialdehyde (MDA) content in the red amaranth increased after 2 h then decreased (after 6 and 10 h) before rising again after 24 h. In the green amaranth, MDA content initially decreased after 2 h before increasing and later decreasing in a zigzag pattern ending in an increase after 24 h. There was an initial steep rise in proline content of green amaranth after 2 h which continued to still rise moderately till 24 h. In the red amaranth the initial rise in proline continued after 2, 6 and 10 h before it stopped. Results also showed that red amaranth gave higher value of superoxide dismutase (SOD) activity as compared with green amaranth in all tested salinity exposure times. The investigation on the expression of four genes assessed through quantitative PCR indicated the efficiency of red amaranth in increasing the expression of SOS1, HKT1, NHX1, and DGR2 genes, which encode adaptation-related proteins under salinity stress. In summary, the current work demonstrated that red amaranth could be an efficient genetic resource in improving salt-tolerant genotypes belonging to Amaranthus genus.

E-cigarettes increase the risk of adenoma formation in murine colorectal cancer model - Ibrahim M. Sayed; Anirban Chakraborty; Kaili Inouye; Leanne Dugan; Stefania Tocci; Ira Advani; Kenneth Park; Samvel Gaboyan; Nikita Kasaraneni; Benjamin Ma; Tapas K. Hazra; Soumita Das; et al. (Archives of Toxicology, 2025)

Foraminiferal biostratigraphy and depositional environment of the late Albian–Cenomanian Al Hilal formation in northeastern Libya - Ibrahim M. Abd El-Gaied; Yasser F. Salama; Mansour H. Al-Hashim; Michael M. Grammer; Sayed M. Abd El-Aziz (Carbonates and Evaporites, 2025)

Berberine-loaded iron oxide nanoparticles alleviate cuprizone-induced astrocytic reactivity in a rat model of multiple sclerosis - Ghadha Ibrahim Fouad; Mostafa Mabrouk; Sara A. M. El-Sayed; Mohamed F. Abdelhameed; Maha Z. Rizk; Hanan H. Beherei (BioMetals, 2025)
Berberine (BBN) is a naturally occurring alkaloid as a secondary metabolite in many plants and exhibits several benefits including neuroprotective activities. However, data on the neuromodulating potential of nanoformulated BBN are still lacking. In the present study, BBN loaded within iron oxide nanoparticles (BBN-IONP) were prepared and characterized by transmission electron microscopy FTIR, X-ray photoelectron spectroscopy particle-size distribution, zeta potential, and HPLC. The remyelinating neuroprotective potential of BBN-IONP relative to free BBN was evaluated against cuprizone (CPZ)-induced neurotoxicity (rats administered 0.2% CPZ powder (w/w) for five weeks). CPZ rats were treated with either free BBN or IONP-BBN (50 mg/kg/day, orally) for 14 days. Cognitive function was estimated using Y-maze. Biochemically, total antioxidant capacity lipid peroxides and reduced glutathione in the brain tissue, as well as, serum interferon-gamma levels were estimated. Moreover, the genetic expression contents of myelin basic protein Matrix metallopeptidase-9 Tumor necrosis factor-α (TNF-α), and S100β were measured. The histopathological patterns and immunohistochemical assessment of Glial Fibrillary Acidic Protein in both cerebral cortex and hippocampus CA1 regions were investigated. CPZ-rats treated with either free BBN or IONP-BBN demonstrated memory restoring, anti-oxidative, anti-inflammatory, anti-astrocytic, and remyelinating activities. Comparing free BBN with IONP-BBN revealed that the latter altered the neuromodulating activities of BBN, showing superior neuroprotective activities of IONP-BBN relative to BBN. In conclusion, both forms of BBN possess neuroprotective potential. However, the use of IONPs for brain delivery and the safety of these nano-based forms need further investigation.

Enhanced simultaneous voltammetric detection of lead, copper, and mercury using a MIL-101(Cr)-(COOH)2@MWCNTs modified glassy carbon electrode - Osama A.S. Rafea; Ali M. Abdel-Aziz; Mostafa A. Sayed; Reda M. Abdelhameed; Ibrahim H.A. Badr (Analytica Chimica Acta, 2025)

Biosorbent silver nanoparticles decorated coffee-ground waste composite for cleaning water and antimicrobial applications - Azza A. Al-Ghamdi; Sherif M. Ibrahim; Xingmei Lu; Jiayu Xin; Ibrahim El-Tantawy El-Sayed; Ahmed A. Galhoum; Swelm. Wageh (Environmental Science and Pollution Research, 2025)

In vivo antischistosomal activity profiling and efficacy of niosomal Spirulina platensis and praziquantel combined remedy against murine Schistosoma mansoni infection - Heba Abdel-Tawab; Shrouk E. Al-Sayed; Fatma I. Abo El-Ela; Amina M. Ibrahim; Olfat A. Hammam; Almahy M. El-Mallah (Veterinary Parasitology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

Dietary supplementation with fermented prebiotics and probiotics can increase growth, immunity, and histological alterations in Pacific whiteleg shrimp (Litopenaeus vannamei) challenged with Vibrio parahaemolyticus - El-Sayed Hemdan Eissa; Heba A. Dowidar; Nawal Al-Hoshani; Narjes Baazaoui; Naheda M. Alshammari; Safia M. A. Bahshwan; Zulhisyam Abdul Kari; Saadiah Ibrahim; Mohammad Bodrul Munir; Ammar AL-Farga; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

As nature's allies: Bee honey outperforms pomegranate and lemon juices in improving physio-biochemistry, antioxidants, RubisCO gene expression, and vase life of Calendula officinalis - Mostafa M. Rady; Marwa S.M. Habib; Ibrahim A.A. Mohamed; Hesham F. Alharby; Taia A.Abd El-Mageed; El‑Sayed M. Desoky; Alaa I.B. Abou-Sreea; Esmat F. Ali (South African Journal of Botany, 2024)

Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

Synthesis, cytotoxicity, anti-inflammatory, anti-metastatic and anti-oxidant activities of novel chalcones incorporating 2-phenoxy-N-arylacetamide and thiophene moieties: induction of apoptosis in MCF7 and HEP2 cells - Nada S. Ibrahim; Hager Ahmed Sayed; Marwa Sharaky; Hadeer M. Diab; Ahmed H. M. Elwahy; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Eight Novel chalcones were synthesized and their structures were confirmed by different spectral tools. All the prepared compounds were subjected to SRB cytotoxic screening against several cancer cell lines. Compound 5c exerted the most promising effect against MCF7 and HEP2 cells with IC 50 values of 9.5 and 12 µg/mL, respectively. Real-time PCR demonstrated the inhibitory effect of compound 5c on the expression level of Antigen kiel 67 (KI-67), Survivin, Interleukin-1beta ( IL-1B ) , Interleukin-6 ( IL-6 ), Cyclooxygenase-2 (COX-2 ) and Protein kinase B (AKT1) genes. Flow-cytometric analysis of the cell cycle indicated that compound 5c stopped the cell cycle at the G0/G1 and G2/M phases in MCF7 and HEP2 treated cells, respectively. ELISA assay showed that Caspase 8, Caspase 9, P53, BAX, and Glutathione (GSH) were extremely activated and Matrix metalloproteinase 2 (MMP2), Matrix metalloproteinase 9 (MMP9), BCL2, Malondialdehyde (MDA), and IL-6 were deactivated in 5c treated MCF7 and HEP2 cells. Wound healing revealed that chalcone 5c reduced the ability to close the scrape wound and decreased the number of migrating MCF7 and HEP2 cells compared to the untreated cells after 48 h. Theoretical molecular modeling against P53 cancer mutant Y220C and Bcl2 showed binding energies of -22.8 and -24.2 Kcal/mole, respectively, which confirmed our ELISA results.

Compilation of secondary metabolites produced by fungal strains identified as Aspergillus flavus var. oryzae (formerly Aspergillus oryzae), with a review of biotechnological applications, and computational studies of their anti-COVID-19 activity - Sabrin R. M. Ibrahim; Flavia Pinzari; Shaimaa G. A. Mohamed; Hazem G. A. Hussein; Abdulrahim A. Alzain; Mohammed A. Almogaddam; Ahmed H. E. Hassan; Selwan M. El-Sayed; Nada A. S. O. AlGhamdi; Gamal A. Mohamed (Mycological Progress, 2024)

Retraction Note: The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2024)

6-Paradol exhibits antimicrobial, anti-quorum sensing and anti-virulence capacities on gram-negative bacteria: In vitro and in vivo studies - Hassan M. Okairy; Abdulrahman E. Koshak; Mahmoud A. Elfaky; Hossam M. Abdallah; Gamal A. Mohamed; Sabrin R.M. Ibrahim; Abdulrahim A. Alzain; El-Sayed Khafagy; Azza A.H. Rajab; Wael A.H. Hegazy (South African Journal of Botany, 2024)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Thunbergia’s Flowers Secondary Metabolites a Natural Armor Against Kidney Damage by Diclofenac - Fatma Sayed Abdel-Aal Farag; Fatma Mohamed Abd El-Mordy; Mona H. Ibrahim; Enas S. Gad; Rania H. M. Soliman; Hend M. Anwar (Cell Biochemistry and Biophysics, 2024)

Facies hierarchy and microscopic features of upper Eocene rock succession, northern Eastern Desert, Egypt: inference on frequent subaerial exposure of Tethys platform and relevant palaeoclimates - Hanan S. Badawy; Soheir H. El-Shazly; Dina M. Sayed; Ibrahim M. Abd El-Gaied; Yasser F. Salama (Carbonates and Evaporites, 2024)

Chamomile Extract Reduces Cardiac Toxicity in Female Mice with Ehrlich Solid Carcinoma - Hamed A. Abosharaf; Amira M. Farag; Abdel Allem H. Abdel Allem; Ibrahim E. T. El-Sayed; Mohamed A. Akela; Ehab Tousson; Eman H. Kandil (Cell Biochemistry and Biophysics, 2024)

Development of an Inflamed High Throughput Stem-cell-based Gut Epithelium Model to Assess the Impact of Annexin A1 - Milena Fronza Broering; Stefania Tocci; Noah T. Sout; Chris Reutelingsperger; Sandra H.P. Farsky; Soumita Das; Ibrahim M. Sayed (Stem Cell Reviews and Reports, 2024)

Neuroprotective potential of Erigeron bonariensis ethanolic extract against ovariectomized/D-galactose-induced memory impairments in female rats in relation to its metabolite fingerprint as revealed using UPLC/MS - Weam W. Ibrahim; Rabab H. Sayed; Mohamed F. Abdelhameed; Enayat A. Omara; Mahmoud I. Nassar; Noha F. Abdelkader; Mohamed A. Farag; Abdelsamed I. Elshamy; Sherif M. Afifi (Inflammopharmacology, 2024)
Erigeron bonariensis is widely distributed throughout the world's tropics and subtropics. In folk medicine, E. bonariensis has historically been used to treat head and brain diseases. Alzheimer’s disease (AD) is the most widespread form of dementia initiated via disturbances in brain function. Herein, the neuroprotective effect of the chemically characterized E. bonariensis ethanolic extract is reported for the first time in an AD animal model. Chemical profiling was conducted using UPLC–ESI-MS analysis. Female rats underwent ovariectomy (OVX) followed by 42 days of D-galactose (D-Gal) administration (150 mg/kg/day, i.p) to induce AD. The OVX/D-Gal-subjected rats received either donepezil (5 mg/kg/day) or E. bonariensis at 50, 100, and 200 mg/kg/day, given 1 h prior to D-Gal. UPLC–ESI-MS analysis identified 42 chemicals, including flavonoids, phenolic acids, terpenes, and nitrogenous constituents. Several metabolites, such as isoschaftoside, casticin, velutin, pantothenic acid, xanthurenic acid, C18-sphingosine, linoleamide, and erucamide, were reported herein for the first time in Erigeron genus. Treatment with E. bonariensis extract mitigated the cognitive decline in the Morris Water Maze test and the histopathological alterations in cortical and hippocampal tissues of OVX/D-Gal-subjected rats. Moreover, E. bonariensis extract mitigated OVX/D-Gal-induced Aβ aggregation, Tau hyperphosphorylation, AChE activity, neuroinflammation (NF-κBp65, TNF-α, IL-1β), and apoptosis (Cytc, BAX). Additionally, E. bonariensis extract ameliorated AD by increasing α7-nAChRs expression, down-regulating GSK-3β and FOXO3a expression, and modulating Jak2/STAT3/NF-ĸB p65 and PI3K/AKT signaling cascades. These findings demonstrate the neuroprotective and memory-enhancing effects of E. bonariensis extract in the OVX/D-Gal rat model, highlighting its potential as a promising candidate for AD management. Graphical Abstract

Automated diagnosis of EEG abnormalities with different classification techniques - Essam Abdellatef; Heba M. Emara; Mohamed R. Shoaib; Fatma E. Ibrahim; Mohamed Elwekeil; Walid El-Shafai; Taha E. Taha; Adel S. El-Fishawy; El-Sayed M. El-Rabaie; Ibrahim M. Eldokany; Fathi E. Abd El-Samie (Medical & Biological Engineering & Computing, 2023)

A hybrid deep learning model for rainfall in the wetlands of southern Iraq - Fehaid Alqahtani; Mostafa Abotaleb; Alhumaima Ali Subhi; El-Sayed M. El-Kenawy; Abdelaziz A. Abdelhamid; Khder Alakkari; Amr Badr; H. K. Al-Mahdawi; Abdelhameed Ibrahim; Ammar Kadi (Modeling Earth Systems and Environment, 2023)

Citrate-containing lemon juice, as an organic substitute for chemical citric acid, proactively improves photosynthesis, antioxidant capacity, and enzyme gene expression in cadmium-exposed Phaseolus vulgaris - Mostafa M. Rady; Hesham F. Alharby; El-Sayed M. Desoky; Ahmed R.M. Maray; Ibrahim A.A. Mohamed; Saad M. Howladar; Yasmine H. Abd Elmohsen; Ahmad Faraz; Shafaqat Ali; Abdelsattar AbdelKhalik (South African Journal of Botany, 2023)

Synergistic effect of trans-zeatin and silymarin on mitigation of cadmium stress in chili pepper through modulating the activity of antioxidant enzymes and gene expressions - Mostafa M. Rady; Khalid S. Alshallash; El-Sayed M. Desoky; Hanan A.A. Taie; Ibrahim A.A. Mohamed; Ali M. El-Badri; Saad M. Howladar; Abdelsattar AbdelKhalik (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Trimetazidine alleviates paclitaxel-induced peripheral neuropathy through modulation of TLR4/p38/NF-κB and klotho protein expression - Asmaa S.A. Hammad; Mohamed M. Sayed-Ahmed; Sara Mohamed Naguib Abdel Hafez; Ahmed R.N. Ibrahim; Mohamed M.A. Khalifa; Mahmoud El-Daly (Chemico-Biological Interactions, 2023)

Dietary Effects of Nano Curcumin on Growth Performances, Body Composition, Blood Parameters and Histopathological Alternation in Red Tilapia (Oreochromis sp.) Challenged with Aspergillus flavus - El-Sayed Hemdan Eissa; Bothaina A. Alaidaroos; Samyah D. Jastaniah; Mohammad Bodrul Munir; Manal E. Shafi; Yasmin M. Abd El-Aziz; Walaa K. Bazina; Saadiah binti Ibrahim; Moaheda E. H. Eissa; Marina Paolucci; Fatima S. Alaryani; Nadia N. B. Abd El-Hamed; et al. (Fishes, 2023)
This research examined the role of nano curcumin (NC) on growth performances, body composition, and blood parameters of red tilapia (Oreochromis sp.) challenged with Aspergillus flavus. Fish (5.0 g ± 0.30) were randomly distributed in four equal groups (20 fish per pond in triplicates) and fed various concentrations of NC fortified with 0 (Control), 40 mg/kg (NC1), 50 mg/kg (NC2), and 60 mg/kg diet (NC3) of nano curcumin. After eight weeks of the feeding trial, the fish were challenged with A. flavus for 15 days, and the cumulative mortality was recorded. Fish fed with different concentrations of NC improved significantly (p 0.05) difference between NC2 and NC3 treatments. However, NC3 exhibited higher performances. Fish feed supplemented with NC decreased the mortality rate when challenged with A. flavus. Hence, dietary supplementation of NC enhanced the growth and health status of Oreochromis sp. and protected it from A. flavus infection. This study suggests the optimum inclusion level of NC is a 50–60 mg/kg diet.

Design and cytotoxic evaluation via apoptotic and antiproliferative activity for novel 11(4-aminophenylamino)neocryptolepine on hepatocellular and colorectal cancer cells - Esraa Tariq Nagy; Abdullah A. S. Ahmed; Elshaymaa I. Elmongy; Saad M. EL-Gendy; Ibrahim Elmadbouh; Ibrahim El Tantawy El Sayed; Mabrouk Attia Abd Eldaim; Ahmed A. El-Gokha (Apoptosis, 2023)

Symbiosis of genus Hydractinia and in situ hermit crab in Kerunia cornuta Mayer-Eymar, 1899 from the Upper Eocene rocks in northwest Qarun Lake, Fayum area, Egypt - Dina M. Sayed; Soheir H. El-Shazly; Yasser F. Salama; Ibrahim M. Abd El-Gaied; Hanan S. Badawy (Journal of African Earth Sciences, 2023)

Evaluation of energy extraction of PV systems affected by environmental factors under real outdoor conditions - Muhammed A. Hassan; Nadjem Bailek; Kada Bouchouicha; Abdelhameed Ibrahim; Basharat Jamil; Alban Kuriqi; Samuel Chukwujindu Nwokolo; El-Sayed M. El-kenawy (Theoretical and Applied Climatology, 2022)
The global agenda to increase the renewable energy share has driven many countries and entities to harness solar energy from solar photovoltaic (PV) systems. However, the power generation of PV systems is strongly affected by climate conditions. Therefore, the main objective of this study is to analyze and predict the power generation of different PV technologies under arid desert climate conditions on an hourly basis. Two areas have been considered as case studies: Adrar in Algeria and Alice Springs in Australia. A total of nine physical models and input parameter combinations from six different power plants have been used and tested for the suitability of the proposed models for predicting the power yield of PV power plants depending on solar irradiance and other meteorological variables. Then, an ensemble learning technique is applied to improve the performance capabilities of the best-fit input combinations. The results reveal that the global irradiance, ambient air temperature, and relative humidity combination are the most related to the PV power output of all technologies under all-sky conditions and provide effective and efficient performance with the proposed ensemble learning, with an estimated accuracy of over 99%.

Neuroprotective Potential of Intranasally Delivered Sulforaphane-Loaded Iron Oxide Nanoparticles Against Cisplatin-Induced Neurotoxicity - Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Mostafa Mabrouk; Kawkab A. Ahmed; Hanan H. Beherei (Neurotoxicity Research, 2022)
Cisplatin (CIS) is a platinum-based chemotherapeutic drug that is widely used to treat cancer. However, its therapeutic efficiency is limited due to its potential to provoke neurotoxicity. Sulforaphane (SF) is a natural phytochemical that demonstrated several protective activities. Iron oxide nanoparticles (Fe 3 O 4 -NPs) could be used as drug carriers. This study aimed to explore the nanotoxic influence of SF-loaded within Fe 3 O 4 -NPs (N.SF), and to compare the neuroprotective potential of both N.SF and SF against CIS-induced neurotoxicity. N.SF or SF was administrated intranasally for 5 days before and 3 days after a single dose of CIS (12 mg/kg/week, i.p.) on the 6 th day. Neuromuscular coordination was assessed using hanging wire and tail-flick tests. Acetylcholinesterase (AChE) activities and markers of oxidative stress were measured in the brain. In addition, the brain iron (Fe) content was estimated. CIS significantly induced a significant increase in AChE activities and lipid peroxides, and a significant decrement in glutathione (GSH) and nitric oxide (NO) contents. CIS elicited impaired neuromuscular function and thermal hyperalgesia. CIS-induced brains displayed a significant reduction in Fe content. Histopathological examination of different brain regions supported the biochemical and behavioral results. Contradict, treatment of CIS-rats with either N.SF or SF significantly decreased AChE activity, mitigated oxidative stress, and ameliorated the behavioral outcome. The histopathological features supported our results. Collectively, N.SF demonstrated superior neuroprotective activities on the behavioral, biochemical, and histopathological (striatum and cerebral cortex) aspects. N.SF could be regarded as a promising “pre-clinical” neuroprotective agent. Furthermore, this study confirmed the safe toxicological profile of Fe 3 O 4 -NPs.

Potential mechanisms underlying the association between type II diabetes mellitus and cognitive dysfunction in rats: a link between miRNA-21 and Resveratrol’s neuroprotective action - Norhan S. El-Sayed; Soha Elatrebi; Rasha Said; Heba F. Ibrahim; Eman M. Omar (Metabolic Brain Disease, 2022)
Cognitive impairment is considered as a typical feature of neurodegenerative diseases in diabetes mellitus (DM). However, the exact link between cognitive dysfunction and diabetes mellitus is still vague. This study aims to investigate some of the mechanisms underlying cognitive impairment that associates diabetes mellitus and insulin resistance. We investigated the role of resveratrol as well on cognitive function in experimentally induced type 2 diabetes highlighting on its influence on the expression of brain miRNA 21. Resveratrol is a naturally occurring, biologically active compound that has numerous significant impacts on the body. Type 2 diabetes mellitus was induced by high fat diet followed a single dose of streptozotocin. Diabetic rats were treated with resveratrol for four weeks. Rats were sacrificed after neurobehavioral testing. Hippocampal tissues were used to assess expression of miRNA 21, GSK and oxidative stress markers. Serum samples were obtained to determine glucose levels, lipid profile and insulin levels. Hippocampal and serum AGEs were measured as well and HOMA IR was calculated. We detected memory impairment and disturbed insulin signaling in diabetic rats. These derangements were reversed by resveratrol treatment partially due to increased expression of miRNA-21. Our study pins the role of miRNA-21 in modulating brain insulin signaling and hence alleviating cognitive dysfunction accompanying diabetes mellitus.

Combined Effect of Prickly Pear Waste Biochar and Azolla on Soil Fertility, Growth, and Yield of Roselle (Hibiscus sabdariffa L.) Plants - Hassan M. Al-Sayed; Ahmed M. Ali; Mahmoud A. Mohamed; Mostafa F. Ibrahim (Journal of Soil Science and Plant Nutrition, 2022)
Although the use of biochar to promote plant growth has been reported by many researchers, the combined effect of prickly pear waste biochar (BC) and Azolla (AZ) in a field experiment on the roselle plants did yet receive attention. Therefore, the study aims to evaluate the effect of biochar and Azolla extract on the growth, production, and quality of roselle plants. The experiment treatments were in a completely randomized block design with three replicates. Biochar was added at rates of 0, 10, and 20 ton ha −1 and AZ was applied at rates of 0, 3, and 6% in addition to a control treatment. Biochar added at high rate (20 ton ha −1 ) significantly increased the fresh and dry weights of sepals by 27.98 and 35.73%, respectively, compared to the control. The corresponding values were significantly increased by 11.89 and 11.85% over the control when Azolla was added at rate of 6%. The interaction effect of both BC and AZ treatments at high rate significantly increased the fresh and dry weight of sepals by 47.16 and 60.59%, respectively, compared to the control. The interaction effect of BC and AZ realized significant effect on soil properties, growth and yield, as well as pigments of roselle plants. This is a good evident means that BC and AZ applications separately or combined are considered promising materials for sustainable organic agriculture and safety food.

Hepatotoxic and Neurotoxic Potential of Iron Oxide Nanoparticles in Wistar Rats: a Biochemical and Ultrastructural Study - Mostafa Mabrouk; Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Maha Z. Rizk; Hanan H. Beherei (Biological Trace Element Research, 2022)

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Ameliorating effects of probiotics on alterations in iron homeostasis and inflammation in COVID-19 - Eman M. El-Sayed; Khadiga S. Ibrahim (Molecular Biology Reports, 2022)

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

Sunshine duration measurements and predictions in Saharan Algeria region: an improved ensemble learning approach - El-Sayed M. El-kenawy; Abdelhameed Ibrahim; Nadjem Bailek; Kada Bouchouicha; Muhammed A. Hassan; Mehdi Jamei; Nadhir Al-Ansari (Theoretical and Applied Climatology, 2022)

Bioethanol production from defatted biomass of Nannochloropsis oculata microalgae grown under mixotrophic conditions - Nashwa A. H. Fetyan; Abo El-Khair B. El-Sayed; Fatma M. Ibrahim; Yasser A. Attia; Mahmoud W. Sadik (Environmental Science and Pollution Research, 2022)

Dietary conjugated linoleic acid and medium-chain triglycerides for obesity management - Khadiga S Ibrahim; Eman M El-Sayed (Journal of Biosciences, 2021)

Optical detection of microplastics in water - Ahmet H. Iri; Malek H. A. Shahrah; Ali M. Ali; Sayed A. Qadri; Talha Erdem; Ibrahim T. Ozdur; Kutay Icoz (Environmental Science and Pollution Research, 2021)

Dose-Dependent Cardioprotective Effect of Hemin in Doxorubicin-Induced Cardiotoxicity Via Nrf-2/HO-1 and TLR-5/NF-κB/TNF-α Signaling Pathways - Marwa M. M. Refaie; Sayed Shehata; Randa Ahmed Ibrahim; Asmaa M. A. Bayoumi; Seham A. Abdel-Gaber (Cardiovascular Toxicology, 2021)

The COVID-19 pandemic: prediction study based on machine learning models - Zohair Malki; El-Sayed Atlam; Ashraf Ewis; Guesh Dagnew; Osama A. Ghoneim; Abdallah A. Mohamed; Mohamed M. Abdel-Daim; Ibrahim Gad (Environmental Science and Pollution Research, 2021)

Risk assessment of horizontal curves using reliability analysis based on Google traffic data - Eman K. Ali; Ibrahim H. Hashim; Sayed A. Shwaly; Zaki M. Zidan; Sherif M. El-Badawy (Innovative Infrastructure Solutions, 2021)

Optimization of Growth Conditions and Biochemical Composition of Microchloropsis salina, Cultured with Three Macroalgal Aqueous Extracts - Mohamed S. Abdel-Kareem; Soad M. Mohy El.Din; El-Sayed M. Ibrahim (Thalassas: An International Journal of Marine Sciences, 2020)

The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A Against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2020)

Phenolic profiling and anti-Alzheimer’s evaluation of Eremobium aegyptiacum - Mona M. Marzouk; Lamyaa F. Ibrahim; Ali M. El-Hagrassi; Dalia B. Fayed; Ahmed Elkhateeb; El-Sayed S. Abdel-Hameed; Sameh R. Hussein (Advances in Traditional Medicine, 2020)

Utilization of Modified Attapulgite for the Removal of Sr(II), Co(II), and Ni(II) Ions from Multicomponent System, Part I: Kinetic Studies - Amira A. Mohammed; Ola A. Abdel Moamen; Sayed S. Metwally; Ahmed M. El-Kamash; Ibrahim Ashour; Mohammed S. Al-Geundi (Environmental Science and Pollution Research, 2020)

Beneficial Effects of Coconut Oil in Treatment of Parkinson’s Disease - K. S. Ibrahim; E. M. El-Sayed (Neurophysiology, 2020)

Syntheses and in silico pharmacokinetic predictions of glycosylhydrazinyl-pyrazolo[1,5-c]pyrimidines and pyrazolo[1,5-c]triazolo[4,3-a]pyrimidines as anti-proliferative agents - Kamal F. M. Atta; Omaima O. M. Farahat; Tareq Q. Al-Shargabi; Mohamed G. Marei; Tamer M. Ibrahim; Adnan A. Bekhit; El Sayed H. El Ashry (Medicinal Chemistry Research, 2019)

Bio and phyto-chemical effect of Amphora coffeaeformis extract against hepatic injury induced by paracetamol in rats - Abo El-Khair B. El-Sayed; Wael M. Aboulthana; Amal M. El-Feky; Noha E. Ibrahim; Mohamed M. Seif (Molecular Biology Reports, 2018)

Toxicological assessment of lambda-cyhalothrin and acetamiprid insecticides formulated mixture on hatchability rate, histological aspects, and protein electrophoretic pattern of Biomphalaria alexandrina (Ehrenberg, 1831) snails - Amina Mohamed Ibrahim; Sara S. M. Sayed; Ibrahim R. A. Shalash (Environmental Science and Pollution Research, 2018)

Assessment of Bioavailability of Some Heavy Metals to Wheat and Faba Bean in Sahl El-Tina, Egypt - A. M. Ali; S. M. Ibrahim; Y. A. Abd El-Hady; A. S. A. Sayed (Agricultural Research, 2018)

Synthesis and antimicrobial activity of newly synthesized 4-substituted-pyrazolo[3,4-d]pyrimidine derivatives - Ahmed M. El-Sayed; Samy M. Ibrahim; Mostafa K. Soltan; Mansour E. Abo-Kul (Medicinal Chemistry Research, 2017)

Nephroprotective efficacy of ceftriaxone against cisplatin-induced subchronic renal fibrosis in rats - Mohamed M. Abdel-Daim; Yasser S. El-Sayed; Mabrouk Abd Eldaim; Abdelazim Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Synthesis, molecular modeling study, preliminary antibacterial, and antitumor evaluation of N-substituted naphthalimides and their structural analogues - Adel S. El-Azab; Amer M. Alanazi; Naglaa I. Abdel-Aziz; Ibrahim A. Al-Suwaidan; Magda A. A. El-Sayed; Magda A. El-Sherbeny; Alaa A.-M. Abdel-Aziz (Medicinal Chemistry Research, 2013)

A new isoflavone from Blepharis ciliaris of an Egyptian origin - Mohamed A. El-Shanawany; Hanaa M. Sayed; Sabrin R. M. Ibrahim; Marwa A. A. Fayed; Mohamed M. Radwan; Samir A. Ross (Medicinal Chemistry Research, 2013)

Neocryptolepine analogues containing N-substituted side-chains at C-11: synthesis and antischistosomicidal activity - Ibrahim El Sayed; Fatem Ramzy; Samia William; Mohamed El Bahanasawy; Mostafa M. Abd El-Sattar (Medicinal Chemistry Research, 2012)

Potential anti-inflammatory activity and ulcerogenicity study of some novel pyrimido[4′,5′:4,5]pyrimido[1,6-a]azepine derivatives - Nehad A. El-Sayed; Fadi M. Awadallah; Nashwa A. Ibrahim; Mohamed T. El-Saadi (Medicinal Chemistry Research, 2012)

Antihypercholesterolaemic effect of ginger rhizome (Zingiber officinale) in rats - El-Sayed M. ElRokh; Nemat A. Z. Yassin; Siham M. A. El-Shenawy; Bassant M. M. Ibrahim (Inflammopharmacology, 2010)